José Joaquín Borda: Manifestations of an intellectual vocation in the 19th century (Anclajes, 2014)
The study of the intellectual and conservative José Joaquín Borda´s poetic development enables the analysis of some key aspects of the Colombian literary dynamics in the nineteenth century. Borda´s close relation with periodical publications and his recurrent attendance to social gatherings —fundamental places for sociability in the Colombian 19th century—, are crucial when examining the particular contexts in which the literary discourse was forged and empowered, during the process of constructing a national identity with certain conservative traits. All in all the analysis of some specific cases will allow the deepening and rebuilding of the social nets that consolidated the cultural life of the studied period.
Keywords: José Joaquín Borda; Colombian literature; Press and Literature; Social gatherings; XIX century